Tanaidacea of the Amundsen and Scotia seas: an unexplored diversity. Issue 1 (15th July 2014) - Pabis, Krzysztof; Błażewicz-Paszkowycz, Magdalena; Jóźwiak, Piotr; Barnes, David K.A.
Abstract The Scotia Arc and Amundsen Sea are contrasting regions within West Antarctica. The Scotia Sea shelf is well studied and central to the origin and diversity of the Southern Ocean benthic fauna, whilst the shelf of Amundsen Sea is one of the least studied shelf areas in the world; a 'white spot' on the map of benthic research. Here we report on the tanaidaceans collected using an epibenthic sledge on two expeditions, BIOPEARL 1 and 2, of the RRS James Clark Ross in 2006 and 2008, respectively. This study represents the first analysis of the tanaidacean fauna of those two basins. Thirty-seven species were found in the Amundsen Sea from 500–1500 m depth and 51 species were found at depths ranging from 200–1600 m in the Scotia Sea. In the Scotia Sea, many species were unique to each of the study sites which may be evidence of allopatric speciation episodes. Site specificity was especially evident for Typhlotanais and Pseudotanais. Only three species were common to both basins. Around 90% of the species were previously undescribed. Our findings increase the number of the tanaidaceans known in the Southern Ocean by 50%.